Bifunctional catalyst, preparation method thereof and method for preparing CO through CO2 hydrogenation catalysis

By developing a dual-function catalyst containing calcium oxide, nickel oxide and metal additives, the problem of incompatibility of CO2 capture and separation and efficient conversion and utilization in the prior art is solved, and efficient adsorption and catalytic conversion of CO2 are achieved, providing innovative green and low-carbon technologies for CO2 emission reduction.

CN119909684APending Publication Date: 2025-05-02CHINA PETROLEUM & CHEMICAL CORP +2

Patent Information

Application Number
CN202311430906.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-31
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

In the prior art, CO2 capture separation and efficient conversion utilization cannot be integrated in a single reactor, resulting in low efficiency in preparing CO2 catalytic hydrogenation.

Method used

A bifunctional catalyst is developed, including calcium oxide as the support and nickel oxide as the metal component, and manganese oxide, zirconium oxide and cerium oxide as metal additives. Through specific mass ratios and preparation methods, a catalyst with rich pore structure is formed.

Benefits of technology

The selective adsorption and catalytic conversion of CO2 into CO are achieved, the CO2 conversion rate and cycle stability are improved, the process conditions and operating parameters are optimized, and an integrated CO2 capture-conversion technology is formed.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004523607480000131
    Figure BDA0004523607480000131
  • Figure BDA0004523607480000132
    Figure BDA0004523607480000132
  • Figure BDA0004523607480000133
    Figure BDA0004523607480000133
Patent Text Reader

Abstract

The invention relates to the technical field of catalysts, and discloses a bifunctional catalyst, a preparation method thereof and a method for preparing CO through CO2 hydrogenation catalysis. The catalyst comprises a carrier, a metal component and a metal auxiliary agent, the metal component and the metal auxiliary agent are loaded on the carrier, the carrier is calcium oxide, the metal component is nickel oxide, and the metal auxiliary agent is selected from one or more of manganese oxide, zirconium oxide and cerium oxide. The invention provides a bifunctional adsorbent-catalyst which can selectively adsorb CO2 and catalyze CO2 into CO, and realizes integration of adsorption decarburization and catalytic regeneration. The bifunctional catalyst has a rich pore channel structure, catalytic reaction is facilitated, regulation and control of the structure and performance of the catalyst are achieved by adding different metal auxiliaries, the catalytic activity is more efficient, and meanwhile the stability and durability of the adsorption catalytic activity are guaranteed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of catalysts, and in particular to a bifunctional catalyst and a preparation method thereof, and a method for preparing CO by catalytic hydrogenation of CO2. Background Art

[0002] Faced with the huge challenges of CO2 emission reduction and climate change, the international community has made many efforts and achieved milestone progress such as the United Nations Framework Convention on Climate Change (UNFCCC), the Kyoto Protocol and the Paris Agreement, and reached consensus on CO2 emission reduction targets, flexibility mechanisms, and 2°C temperature rise.

[0003] Currently, CCUS technology faces key issues such as the independence of CO2 capture and CO2 thermochemical conversion and utilization processes, high infrastructure costs for CO2 transportation pipelines, and high energy consumption for regeneration and conversion. This means that CO2 capture and separation and conversion and utilization rely on independent adsorption or catalytic materials, independent reaction devices, and higher energy consumption requirements. How to couple CO2 capture and CO2 utilization processes and realize CO2 capture and separation and efficient conversion and utilization in a single reactor is still a challenge.

[0004] The existing catalysts used for the catalytic hydrogenation of CO2 to produce CO have the problem that CO2 capture and separation and efficient conversion and utilization cannot be integrated. Summary of the invention

[0005] The purpose of the present invention is to overcome the problem of poor catalyst effect of the prior art CO2 adsorption-catalytic conversion of CO2 to produce CO coupling technology, and to provide a bifunctional catalyst and a preparation method and a method for preparing CO by catalytic hydrogenation of CO2.

[0006] In order to achieve the above-mentioned purpose, the first aspect of the present invention provides a bifunctional catalyst, wherein the catalyst comprises: a carrier and a metal component and a metal additive loaded on the carrier, wherein the carrier is calcium oxide, the metal component is nickel oxide, and the metal additive is selected from one or more of manganese oxide, zirconium oxide and cerium oxide, wherein the mass ratio of calcium oxide to nickel oxide is 0.5-1:1.

[0007] A second aspect of the present invention provides a method for preparing a bifunctional catalyst, wherein the method comprises:

[0008] (1) subjecting a nickel salt, a complexing agent and a calcium salt to a complexing reaction to obtain a complexing solution;

[0009] (2) impregnating the metal M oxide into the complexing solution to obtain a mixture;

[0010] (3) drying and calcining the mixture to obtain the bifunctional catalyst;

[0011] Wherein, M is at least one of Mn, Zr and Ce.

[0012] The third aspect of the present invention provides a bifunctional catalyst prepared by the preparation method.

[0013] A fourth aspect of the present invention provides a method for preparing CO by catalytic hydrogenation of CO2, wherein the method comprises: first subjecting a gas containing CO2 to a catalytic hydrogenation reaction in the presence of H2 and a catalyst, wherein the catalyst used is the bifunctional catalyst.

[0014] Through the above technical scheme, the present invention provides a bifunctional adsorbent-catalyst that can selectively adsorb CO2 and catalyze CO2 to CO, realizing adsorption decarbonization and catalytic regeneration in one. The bifunctional catalyst has a rich pore structure, which is conducive to the catalytic reaction. By adding different metal additives, the catalyst structure and performance are regulated, making the catalytic activity more efficient, while also ensuring the stability and durability of the adsorption catalytic activity. In terms of process: improve the CO2 conversion rate and cycle stability of the bifunctional material, optimize the process conditions and operating parameters, determine the CO2 capture-conversion integrated technology process scheme, and form an innovative green and low-carbon technology with independent intellectual property rights. DETAILED DESCRIPTION

[0015] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0016] The first aspect of the present invention provides a bifunctional catalyst, wherein the catalyst comprises: a carrier and a metal component and a metal additive loaded on the carrier, wherein the carrier is calcium oxide, the metal component is nickel oxide, and the metal additive is selected from one or more of manganese oxide, zirconium oxide and cerium oxide, wherein the mass ratio of calcium oxide to nickel oxide is 0.5-1:1.

[0017] In the present invention, the catalyst contains the above components, which is beneficial to the regulation of the catalyst structure and performance, making the reaction activity of the bifunctional catalyst more efficient, while also ensuring the stability and durability of the adsorption catalytic activity, which is beneficial to the catalytic reaction.

[0018] In some specific embodiments of the present invention, based on the total weight of the catalyst, the content of calcium oxide is 30-50wt%, preferably 35-45wt%; the content of nickel oxide is 45-60wt%, preferably 50-60wt%; the content of metal additive is 1-20wt%, preferably 5-10wt%.

[0019] In the present invention, the bifunctional catalyst has a rich pore structure through the combination of the carrier and the metal components and metal additives loaded on the carrier, which is beneficial to the catalytic reaction. At the same time, by adding different metal additives, the catalyst structure and performance are regulated, making the catalytic activity more efficient. At the same time, the catalyst content range limited in the present application also ensures the stability and durability of the adsorption catalytic activity, and can realize CO2 capture and adsorption saturation followed by hydrogenation conversion. It can not only efficiently and selectively adsorb CO2, but also catalytically convert the adsorbed CO2 into CO, realizing adsorption decarbonization and catalytic regeneration in one.

[0020] In some specific embodiments of the present invention, preferably, the mass ratio of calcium oxide to nickel oxide is 0.6-0.8:1. Limiting the mass ratio of calcium oxide to nickel oxide to 0.6-0.8:1 is beneficial to the regulation of the catalyst structure and performance, making the reaction activity of the bifunctional catalyst more efficient, while also ensuring the stability and durability of the adsorption catalytic activity, which is beneficial to the catalytic reaction.

[0021] In some specific embodiments of the present invention, preferably, the metal additive contains manganese oxide, and may also contain zirconium oxide and / or cerium oxide. When the added metal additive contains manganese oxide, the catalyst has a higher CO2 adsorption amount and conversion rate, as well as a higher CO production, and the catalytic effect of the catalyst is better. Preferably, the metal additive contains manganese oxide, and then contains zirconium oxide and / or cerium oxide. The content of the metal additive is preferably 8wt%, the catalyst has a higher CO2 adsorption amount and conversion rate, as well as a higher CO production, and the catalytic effect of the catalyst is better.

[0022] In some specific embodiments of the present invention, the average pore size of the catalyst is 2-15 nm, and the specific surface area is 10-30 m 2 / g, when the obtained catalyst has this pore size and specific surface area, more active points are utilized and the amount of CO2 adsorbed gas in the pores is large, making the catalytic activity more efficient and the CO production higher.

[0023] A second aspect of the present invention provides a method for preparing a bifunctional catalyst, characterized in that the method comprises:

[0024] (1) subjecting a nickel salt, a complexing agent and a calcium salt to a complexing reaction to obtain a complexing solution;

[0025] (2) impregnating the metal M oxide into the complexing solution to obtain a mixture;

[0026] (3) drying and calcining the mixture to obtain the bifunctional catalyst;

[0027] Wherein, M is at least one of Mn, Zr and Ce.

[0028] In some specific embodiments of the present invention, the nickel salt is selected from one or more of nickel nitrate, nickel acetate, and nickel carbonate.

[0029] In some specific embodiments of the present invention, the complexing agent is one or more of citric acid, ammonium citrate, oxalic acid, and ammonium oxalate.

[0030] In some specific embodiments of the present invention, the M preferably contains Mn, and may also contain Zr and / or Ce. Preferably, the M contains Mn and contains Zr and / or Ce.

[0031] In some specific embodiments of the present invention, the method for preparing the calcium salt comprises: mixing carbide slag with propionic acid, and vacuum filtering the mixed solution to obtain a calcium salt aqueous solution.

[0032] In some specific embodiments of the present invention, the mass ratio of the carbide slag to propionic acid is 1:1-5.

[0033] In some specific embodiments of the present invention, relative to 1 g of carbide slag, the nickel salt is 10-30 mmol, the complexing agent is 10-30 mmol, and the metal M oxide is 0.01-0.2 g, preferably 0.082-0.164 g.

[0034] In some specific embodiments of the present invention, the molar ratio of the complexing agent to the calcium salt is 1:1.

[0035] In some specific embodiments of the present invention, the drying temperature is 100-130° C., and the drying time is 10-18 h.

[0036] In some specific embodiments of the present invention, the calcination temperature is 800-900° C., and the calcination time is 4-6 hours.

[0037] The third aspect of the present invention provides a bifunctional catalyst prepared by the preparation method.

[0038] The fourth aspect of the present invention provides a method for preparing CO by catalytic hydrogenation of CO2, wherein the method comprises: first subjecting a gas containing CO2 to a catalytic hydrogenation reaction in the presence of H2 and a catalyst, wherein the catalyst is the bifunctional catalyst described in the first aspect or the third aspect.

[0039] In some specific embodiments of the present invention, the reaction temperature is 600-700°C and the CO2 concentration is 5-40 vol%.

[0040] In some specific embodiments of the present invention, the CO2 adsorption capacity of the bifunctional catalyst is 4.68-8.39 mmol / g, the CO production is 2.96-6.23 mmol / g, and the CO2 conversion rate is 55.53-76.39%.

[0041] The present invention will be described in detail below through examples.

[0042] In the following examples and comparative examples, if no specific conditions are specified, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. The reagents or instruments used, if no manufacturer is specified, are all conventional products that can be obtained through commercial channels.

[0043] Example 1

[0044] (1) 1 g of carbide slag was mixed with 20 mmol of propionic acid solution (solid-liquid ratio of 1:20) and stirred for 2 hours. The mixture was filtered out through a vacuum filtration system to extract the Ca ions.

[0045] (2) Then, 20 mmol of nickel nitrate and 20 mmol of citric acid were added to the filtrate rich in calcium ions and stirred at 80° C. for 2 hours for complexation. The stoichiometric ratio of citric acid to Ca ions was 1:1.

[0046] (3) Ni-CaO composite bifunctional material was prepared by oxidative treatment / impregnation of 0.131 g manganese oxide combined with citric acid complexation.

[0047] (4) the mixture was then dried in a constant temperature drying oven at 110° C. for 12 hours, and then the mixture was placed in a muffle furnace and calcined at 850° C. (heating rate: 3° C. / min) for 5 hours to obtain a bifunctional catalyst A1;

[0048] Based on the total weight of the catalyst, the content of calcium oxide is 39wt%; the content of nickel oxide is 53wt%; the content of metal additive manganese oxide is 8wt%; and the mass ratio of calcium oxide to nickel oxide is 0.75:1.

[0049] Example 2

[0050] (1) 1 g of carbide slag was mixed with 20 mmol of propionic acid solution (solid-liquid ratio of 1:20) and stirred for 2 hours. The mixture was filtered out through a vacuum filtration system to extract the Ca ions.

[0051] (2) Then, 20 mmol of nickel nitrate and 20 mmol of citric acid were added to the filtrate rich in calcium ions and stirred at 80° C. for 2 hours for complexation. The stoichiometric ratio of citric acid to Ca ions was 1:1.

[0052] (3) Ni-CaO composite dual-functional material was prepared by acidification / impregnation of 0.131 g cerium oxide combined with citric acid complexation.

[0053] (4) The mixture was then dried in a constant temperature drying oven at 110°C for 12 hours, and then the mixture was placed in a muffle furnace and calcined at 850°C (heating rate: 3°C / min) for 5 hours. The obtained bifunctional catalyst was marked as A2;

[0054] Based on the total weight of the catalyst, the content of calcium oxide is 39wt%; the content of nickel oxide is 53wt%; the content of metal auxiliary agent cerium oxide is 8wt%; and the mass ratio of calcium oxide to nickel oxide is 0.75:1.

[0055] Example 3

[0056] (1) 1 g of carbide slag was mixed with 20 mmol of propionic acid solution (solid-liquid ratio of 1:20) and stirred for 2 hours. The mixture was filtered out through a vacuum filtration system to extract the Ca ions.

[0057] (2) Subsequently, 20 mmol of nickel nitrate and 20 mmol of citric acid were added to the filtrate rich in calcium ions and stirred at 80°C for 2 hours for complexation. The stoichiometric ratio of citric acid to Ca ions was 1:1.

[0058] (3) Ni-CaO composite dual-functional material was prepared by acidification / impregnation of 0.131 g zirconium oxide combined with citric acid complexation.

[0059] (4) The mixture was then dried in a constant temperature drying oven at 110°C for 12 hours, and then the mixture was placed in a muffle furnace and calcined at 850°C (heating rate: 3°C / min) for 5 hours. The obtained bifunctional catalyst was marked as A3;

[0060] Based on the total weight of the catalyst, the content of calcium oxide is 39wt%; the content of nickel oxide is 53wt%; the content of metal additive zirconium oxide is 8wt%; and the mass ratio of calcium oxide to nickel oxide is 0.75:1.

[0061] Example 4

[0062] (1) 1 g of carbide slag was mixed with 20 mmol of propionic acid solution (solid-liquid ratio of 1:20) and stirred for 2 hours. The mixture was filtered out through a vacuum filtration system to extract the Ca ions.

[0063] (2) Then, 20 mmol of nickel nitrate and 20 mmol of citric acid were added to the filtrate rich in calcium ions and stirred at 80° C. for 2 hours for complexation. The stoichiometric ratio of citric acid to Ca ions was 1:1.

[0064] (3) Ni-CaO composite bifunctional material was prepared by oxidizing / impregnating 0.05 g manganese oxide and combining it with citric acid complexation.

[0065] (4) The mixture was then dried in a constant temperature drying oven at 110°C for 12 hours, and then the mixture was placed in a muffle furnace and calcined at 850°C (heating rate: 3°C / min) for 5 hours. The obtained bifunctional catalyst was marked as A4;

[0066] Based on the total weight of the catalyst, the content of calcium oxide is 41.5wt%; the content of nickel oxide is 55.5wt%; the content of metal additive manganese oxide is 3wt%; and the mass ratio of calcium oxide to nickel oxide is 0.75:1.

[0067] Example 5

[0068] (1) 1 g of carbide slag was mixed with 20 mmol of propionic acid solution (solid-liquid ratio of 1:20) and stirred for 2 hours. The mixture was filtered out through a vacuum filtration system to extract the Ca ions.

[0069] (2) Then, 20 mmol of nickel nitrate and 20 mmol of citric acid were added to the filtrate rich in calcium ions and stirred at 80° C. for 2 hours for complexation. The stoichiometric ratio of citric acid to Ca ions was 1:1.

[0070] (3) Ni-CaO composite bifunctional material was prepared by acidification / impregnation of 0.082 g manganese oxide and chelation with citric acid.

[0071] (4) The mixture was then dried in a constant temperature drying oven at 110°C for 12 hours, and then the mixture was placed in a muffle furnace and calcined at 850°C (heating rate: 3°C / min) for 5 hours. The obtained bifunctional catalyst was marked as A5;

[0072] Based on the total weight of the catalyst, the content of calcium oxide is 40.3wt%; the content of nickel oxide is 54.5wt%; the content of metal additive manganese oxide is 5wt%; and the mass ratio of calcium oxide to nickel oxide is 0.75:1.

[0073] Example 6

[0074] (1) 1 g of carbide slag was mixed with 20 mmol of propionic acid solution (solid-liquid ratio of 1:20) and stirred for 2 hours. The mixture was filtered out through a vacuum filtration system to extract the Ca ions.

[0075] (2) Then, 20 mmol of nickel nitrate and 20 mmol of citric acid were added to the filtrate rich in calcium ions and stirred at 80° C. for 2 hours for complexation. The stoichiometric ratio of citric acid to Ca ions was 1:1.

[0076] (3) Ni-CaO composite bifunctional material was prepared by acidification / impregnation of 0.164 g manganese oxide and combined with citric acid complexation.

[0077] (4) The mixture was then dried in a constant temperature drying oven at 110°C for 12 hours, and then the mixture was placed in a muffle furnace and calcined at 850°C (heating rate: 3°C / min) for 5 hours. The resulting bifunctional catalyst was labeled A6;

[0078] Based on the total weight of the catalyst, the content of calcium oxide is 38wt%; the content of nickel oxide is 52wt%; the content of metal additive manganese oxide is 10wt%; and the mass ratio of calcium oxide to nickel oxide is 0.75:1.

[0079] Example 7

[0080] (1) 1.34 g of carbide slag was mixed with 20 mmol of propionic acid solution (solid-to-liquid ratio of 1:20) and stirred for 2 hours. The mixture was filtered out through a vacuum filtration system to extract Ca ions.

[0081] (2) Then, 20 mmol of nickel nitrate and 20 mmol of citric acid were added to the filtrate rich in calcium ions and stirred at 80° C. for 2 hours for complexation. The stoichiometric ratio of citric acid to Ca ions was 1:1.

[0082] (3) Ni-CaO composite bifunctional material was prepared by acidification / impregnation of 0.152 g manganese oxide combined with citric acid complexation.

[0083] (4) the mixture was then dried in a constant temperature drying oven at 110° C. for 12 hours, and then the mixture was placed in a muffle furnace and calcined at 850° C. (heating rate: 3° C. / min) for 5 hours to obtain a bifunctional catalyst A7;

[0084] Based on the total weight of the catalyst, the content of calcium oxide is 46wt%; the content of nickel oxide is 46wt%; the content of metal additive manganese oxide is 8wt%; and the mass ratio of calcium oxide to nickel oxide is 1:1.

[0085] Example 8

[0086] (1) 0.7 g of carbide slag was mixed with 20 mmol of propionic acid solution (solid-to-liquid ratio of 1:20) and stirred for 2 hours. The mixture was filtered out through a vacuum filtration system to extract Ca ions.

[0087] (2) Then, 20 mmol of nickel nitrate and 20 mmol of citric acid were added to the filtrate rich in calcium ions and stirred at 80° C. for 2 hours for complexation. The stoichiometric ratio of citric acid to Ca ions was 1:1.

[0088] (3) Ni-CaO composite bifunctional material was prepared by oxidative treatment / impregnation of 0.115 g manganese oxide combined with citric acid complexation.

[0089] (4) the mixture was then dried in a constant temperature drying oven at 110° C. for 12 hours, and then the mixture was placed in a muffle furnace and calcined at 850° C. (heating rate: 3° C. / min) for 5 hours to obtain a bifunctional catalyst A8;

[0090] Based on the total weight of the catalyst, the content of calcium oxide is 31wt%; the content of nickel oxide is 62wt%; the content of metal additive manganese oxide is 7wt%; and the mass ratio of calcium oxide to nickel oxide is 0.5:1.

[0091] Comparative Example 1

[0092] (1) 1 g of carbide slag was mixed with 20 mmol of propionic acid solution (solid-liquid ratio of 1:20) and stirred for 2 hours. The mixture was filtered out through a vacuum filtration system to extract the Ca ions.

[0093] (2) Then, 20 mmol of nickel nitrate and 20 mmol of citric acid were added to the filtrate rich in calcium ions and stirred at 80° C. for 2 hours for complexation. The stoichiometric ratio of citric acid to Ca ions was 1:1.

[0094] (3) The mixture was then dried in a constant temperature drying oven at 110°C for 12 hours, and then calcined in a muffle furnace at 850°C (heating rate: 3°C / min) for 5 hours. The resulting bifunctional catalyst was labeled B1.

[0095] Comparative Example 2

[0096] (1) 0.51 g of carbide slag was mixed with 20 mmol of propionic acid solution (solid-to-liquid ratio of 1:20) and stirred for 2 hours. The mixture was filtered out through a vacuum filtration system to extract Ca ions.

[0097] (2) Then, 20 mmol of nickel nitrate and 20 mmol of citric acid were added to the filtrate rich in calcium ions and stirred at 80° C. for 2 hours for complexation. The stoichiometric ratio of citric acid to Ca ions was 1:1.

[0098] (3) Ni-CaO composite bifunctional material was prepared by acidification / impregnation of 0.1 g manganese oxide combined with citric acid complexation.

[0099] (4) the mixture was then dried in a constant temperature drying oven at 110° C. for 12 hours, and then the mixture was placed in a muffle furnace and calcined at 850° C. (heating rate: 3° C. / min) for 5 hours to obtain a bifunctional catalyst B2;

[0100] Based on the total weight of the catalyst, the content of calcium oxide is 21.2wt%; the content of nickel oxide is 70.8wt%; the content of metal additive manganese oxide is 8wt%; and the mass ratio of calcium oxide to nickel oxide is 0.3:1.

[0101] Comparative Example 3

[0102] (1) 1.99 g of carbide slag was mixed with 20 mmol of propionic acid solution (solid-to-liquid ratio of 1:20) and stirred for 2 hours. The mixture was filtered out through a vacuum filtration system to extract Ca ions.

[0103] (2) Then, 20 mmol of nickel nitrate and 20 mmol of citric acid were added to the filtrate rich in calcium ions and stirred at 80° C. for 2 hours for complexation. The stoichiometric ratio of citric acid to Ca ions was 1:1.

[0104] (3) Ni-CaO composite bifunctional material was prepared by oxidizing / impregnating 0.28 g manganese oxide and combining it with citric acid complexation.

[0105] (4) the mixture was then dried in a constant temperature drying oven at 110° C. for 12 hours, and then the mixture was placed in a muffle furnace and calcined at 850° C. (heating rate: 3° C. / min) for 5 hours to obtain a bifunctional catalyst B3;

[0106] Based on the total weight of the catalyst, the content of calcium oxide is 55.2wt%; the content of nickel oxide is 36.8wt%; the content of metal additive manganese oxide is 8wt%; and the mass ratio of calcium oxide to nickel oxide is 1.5:1.

[0107] Test Example 1

[0108] Nitrogen adsorption-desorption measurements (BET method) can be used to determine the specific surface area and pore size of the catalyst.

[0109] According to the above test method, the average pore size and specific surface area of ​​the catalyst were obtained, as shown in Table 1.

[0110] Table 1

[0111] catalyst Average pore size / nm <![CDATA[Specific surface area / m 2 / g]]> A1 2.10 24.19 A2 2.11 28.23 A3 2.56 21.62 A4 2.57 21.62 A5 2.11 29.34 A6 2.58 28.33 A7 12.33 26.98 A8 13.10 24.54 B1 9.11 12.40 B2 14.56 11.25 B3 10.45 13.00

[0112] Test Example 2

[0113] (1) Pretreatment process: First, 0.5 g of Ni-CaO dual-functional material was weighed, the sample was placed in a fixed bed reactor and the reactor was heated to 650° C. at 10° C. / min in pure N2 (180 mL / min). Subsequently, the sample was pretreated in 5% H2 / N2 (180 mL / min) for 2 h, and after the pretreatment, pure N2 was purged for 5 min to exhaust the residual gas in the pipeline.

[0114] (2) CO2 adsorption process: The inlet gas flow was switched to 10 vol% CO2 / N2 (180 mL / min) and maintained for 30 minutes for CO2 adsorption. Once the adsorption process was completed, the gas flow was switched to pure N2 to purge the reactor for 5 minutes.

[0115] (3) In-situ hydrogenation reverse water gas conversion process: A reducing gas of 5 vol% H2 / N2 (180 mL / min) was introduced to realize CO2 desorption and hydrogenation catalysis of Ni-CaO dual-functional material. Once the hydrogenation catalysis process was completed, the reactor was purged in a pure N2 flow for 5 minutes. By repeating the above CO2 adsorption and in-situ hydrogenation reverse water gas conversion processes, cyclic CO2 adsorption and in-situ hydrogenation tests can be carried out to evaluate the working stability of Ni-CaO. The changes in the concentration of each gas during CO2 adsorption and in-situ hydrogenation catalysis were recorded in real time by an online gas analyzer (MRU) connected to the reactor outlet.

[0116] Performance evaluation indicators:

[0117] (1) CO2 adsorption capacity of Ni-CaO bifunctional material

[0118] The amount of CO2 adsorption is used to evaluate the CO2 adsorption capacity of the dual-functional material. The specific formula is shown in 1, and the CO2 capture efficiency calculation method is shown in formula 2:

[0119]

[0120]

[0121] in, represents the CO2 adsorption amount, mmol CO2 / g DFMs; Q represents the reaction gas flow rate, mL / min; ρ represents the CO2 density, kg / m 3 ; m represents the mass of dual-function material, g; V m represents the gas molar volume, 22.4L / mol; M represents the relative molecular weight of CO2; C in and C out represents the CO2 concentration at the inlet and outlet of the fixed bed system, vol.%, and t represents the time, min. The time limit of the capture efficiency is 5 min.

[0122] (2) In-situ hydrogenation conversion capability of dual-functional materials

[0123] The CO production and CO2 conversion rate are used to evaluate the in-situ hydrogenation reverse water gas conversion capability of the dual-functional material. The specific formulas are shown in 1 and 2 respectively:

[0124]

[0125]

[0126] Among them, q CO Indicates CO production, mmol CO / g DFMs; C CO represents the CO concentration at the outlet of the fixed bed system, vol.%; Indicates CO2 conversion rate, %.

[0127] According to the above test method, the adsorption catalytic performance results of the catalyst were obtained, as shown in Table 2.

[0128] Table 2

[0129] catalyst <![CDATA[CO2 adsorption capacity / mmol / g]]> CO production / mmol / g Conversion rate / % A1 6.74 5.22 77.45 A2 5.21 3.31 63.53 A3 6.01 3.75 62.40 A4 6.23 4.25 68.22 A5 6.55 4.85 74.05 A6 6.01 3.89 64.73 A7 5.01 3.27 65.27 A8 4.87 2.61 53.59 B1 5.33 2.96 55.53 B2 3.11 0.43 13.83 B3 1.21 0.34 28.01

[0130] The catalyst A1 of Example 1 was tested according to the above test method to obtain the effect of different carbon dioxide concentrations on the adsorption catalytic performance, as shown in Table 3.

[0131] Table 3

[0132] <![CDATA[CO2 concentration / wt%]]> <![CDATA[CO2 adsorption amount / mmol / g]]> CO production / mmol / g Conversion rate / % 10 6.74 5.22 77.45 20 7.56 5.86 77.51 30 7.85 6.05 77.07 40 8.39 6.23 74.26

[0133] The catalyst A1 of Example 1 was tested according to the above test method to obtain the effect of different reaction temperatures on the adsorption catalytic performance, as shown in Table 4.

[0134] Table 4

[0135] Temperature / ℃ <![CDATA[CO2 adsorption amount / mmol / g]]> CO production / mmol / g Conversion rate / % 500 4.68 2.95 63.03 600 6.52 4.56 69.94 650 6.74 5.22 77.45 700 6.82 5.21 76.39

[0136] Comparative Example Result Description:

[0137] (1) Examples The feasibility and applicability of the present invention were verified by studying different types of metal oxide additives, different addition amounts, different adsorbed gas concentrations and different reaction temperatures.

[0138] (2) Through the study of different types of oxidative metal additives, it was found that the Ni-CaO-MnO2-8 catalyst showed the highest CO2 adsorption capacity (6.74 mmol / g) and CO production (5.22 mmol / g), as well as the highest conversion rate (77.45%), indicating that the catalyst has excellent catalytic performance and selectivity.

[0139] (3) As the amount of MnO2 added increases from 3% to 10%, the CO2 adsorption capacity increases first and then decreases, indicating that excessive addition will lead to pore blockage and affect the adsorption performance. At the same time, the conversion rate also increases first and then decreases, indicating that excessive addition of metal oxides will cover the active sites and reduce the reduction performance.

[0140] (4) Under different CO2 concentrations, the bifunctional catalyst exhibited different CO2 adsorption amounts and CO production. At higher CO2 concentrations, the catalyst had better adsorption performance. However, under the operating conditions of 40 vol% CO2 concentration, the CO production decreased, which may be related to the excessive coverage of catalytic sites by carbonates under high CO2 concentration conditions.

[0141] (5) The experimental results show that at 650°C, the Ni-CaO-MnO2-8 catalyst exhibits higher CO2 adsorption and CO production. According to thermodynamic calculations, the higher the temperature, the lower the conversion rate of the CaO component. Considering that temperature also affects the adsorption kinetics, based on the experimental data, the adsorption amount may be more affected by kinetics. In the catalytic process, a temperature of 650°C is conducive to the reaction. The experimental results show that at this temperature, the yield is higher, which is consistent with the results of theoretical thermodynamic calculations.

[0142] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A bifunctional catalyst, characterized in that: The catalyst comprises: a carrier and a metal component and a metal additive loaded on the carrier, wherein the carrier is calcium oxide, the metal component is nickel oxide, and the metal additive is selected from one or more of manganese oxide, zirconium oxide and cerium oxide, wherein the mass ratio of calcium oxide to nickel oxide is 0.5-1:

1.

2. The catalyst according to claim 1, characterized in that Based on the total weight of the catalyst, the content of calcium oxide is 30-50wt%, preferably 35-45wt%; the content of nickel oxide is 45-60wt%, preferably 50-60wt%; the content of metal additive is 1-20wt%, preferably 5-10wt%; Preferably, the mass ratio of calcium oxide to nickel oxide is 0.6-0.8:

1.

3. The catalyst according to claim 1 or 2, characterized in that The average pore size of the catalyst is 2-15 nm, and the specific surface area is 10-30 m 2 / g.

4. A method for preparing a bifunctional catalyst, characterized in that: The method includes: (1) subjecting a nickel salt, a complexing agent and a calcium salt to a complexing reaction to obtain a complexing solution; (2) impregnating the metal M oxide into the complexing solution to obtain a mixture; (3) drying and calcining the mixture to obtain the bifunctional catalyst; Wherein, M is at least one of Mn, Zr and Ce.

5. The preparation method according to claim 4, characterized in that: The nickel salt is selected from one or more of nickel nitrate, nickel acetate, and nickel carbonate; Preferably, the complexing agent is one or more of citric acid, ammonium citrate, oxalic acid and ammonium oxalate.

6. The preparation method according to claim 4 or 5, characterized in that: The drying temperature is 100-130°C, and the drying time is 10-18h; Preferably, the calcination temperature is 800-900° C., and the calcination time is 4-6 hours.

7. The preparation method according to any one of claims 4 to 6, characterized in that: The preparation method of the calcium salt comprises: mixing carbide slag with propionic acid, and filtering the mixed solution by vacuum filtration to obtain a calcium salt aqueous solution; Preferably, the mass ratio of the carbide slag to propionic acid is 1:1-5.

8. The preparation method according to claim 7, characterized in that: Relative to 1g of carbide slag, the nickel salt is 10-30mmol, the complexing agent is 10-30mmol, and the metal M oxide is 0.01-0.2g, preferably 0.082-0.164g.

9. A bifunctional catalyst obtained by the preparation method according to any one of claims 4 to 8.

10. A method for preparing CO by catalytic hydrogenation of CO2, characterized in that: The method comprises: subjecting a gas containing CO2 to a hydrogenation catalytic reaction in the presence of H2 and a catalyst, wherein the catalyst is a bifunctional catalyst as described in any one of claims 1-3 and 9.

11. The method according to claim 10, characterized in that The temperature of the hydrogenation catalytic reaction is 600-700° C., and the CO2 concentration in the gas is 10-40 vol%.

Citation Information

Patent Citations

  • Methanation catalyst with high nickel oxide content and preparation method thereof

    CN103480381A

  • Bifunctional catalyst applied to integration of CO2 capture and methanation in flue gas

    CN113634257A

  • Preparation method and application of catalyst for preparing synthesis gas by coupling calcium cycle carbon dioxide capture and methane dry reforming

    CN115090291A

  • Porous adsorption and catalysis bifunctional material as well as preparation method and application thereof

    CN115445622A

Cited By

  • Difunctional composite material as well as preparation method and application thereof

    CN120437945A